2021
DOI: 10.1093/jas/skab024
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin and mineral supplementation and rate of gain during the first trimester of gestation affect concentrations of amino acids in maternal serum and allantoic fluid of beef heifers

Abstract: The objective of this study was to evaluate the effects of feeding vitamin and mineral (VTM) supplement and (or) rate of gain (GAIN) during early gestation on amino acid (AA) concentrations in allantoic (ALF) and amniotic fluid (AMF) and maternal serum. Seventy-two crossbred Angus heifers (initial BW = 359.5 ± 7.1 kg) were randomly assigned to one of four treatments in a 2 × 2 factorial arrangement with main effects of vitamin and mineral supplement (VTM or NoVTM) and rate of gain (GAIN; low gain [LG], 0.28 kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 33 publications
3
46
0
Order By: Relevance
“…The ARG2 protein is involved in the conversion of Larginine into L-ornithine, which is a precursor to polyamines that support cell proliferation [74], whereas MTR catalyzes the final step in methionine biosynthesis [75]. Menezes et al [25] reported increased concentrations of methionine and arginine in allantoic fluid in response to vitamin supplementation and a moderate rate of gain when evaluating the pregnant heifers used in the current study, which further supports the current findings.…”
Section: Pathways Underlying Cotyledonary Differential Gene Expressionsupporting
confidence: 87%
See 2 more Smart Citations
“…The ARG2 protein is involved in the conversion of Larginine into L-ornithine, which is a precursor to polyamines that support cell proliferation [74], whereas MTR catalyzes the final step in methionine biosynthesis [75]. Menezes et al [25] reported increased concentrations of methionine and arginine in allantoic fluid in response to vitamin supplementation and a moderate rate of gain when evaluating the pregnant heifers used in the current study, which further supports the current findings.…”
Section: Pathways Underlying Cotyledonary Differential Gene Expressionsupporting
confidence: 87%
“…On the other hand, fetal liver weight was greater (p-value = 0.05) from dams fed VTM than NoVTM [27]. Likewise, amino acid concentrations of maternal serum and allantoic and amniotic fluid in the same samples used in the current study were affected by vitamin and mineral supplementation and/or rate of gain [25]. Evidence suggests that biological mechanisms regulating normal growth, development, and nutrient utilization are programmed in utero for postnatal growth and adult function even during the earliest stages of development [40].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although the role of maternal nutrition in developmental programming in cattle has been relatively well appreciated (McLean et al, 2017; Caton et al, 2019; Crouse et al, 2019; Menezes et al, 2021), the potential involvement of the maternal microbiota in fetal programming and offspring microbiome development remains largely unexplored. Considering the current evidence, it is important to explore whether bovine maternal nutrition/microbiome during pregnancy influences feto-maternal crosstalk, subsequently influencing offspring microbiome development.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used 16S rRNA gene sequencing to characterize the nasopharyngeal, ruminal and vaginal microbiota of virgin yearling heifers from dams given different nutritional diets during their first trimester of gestation, and in pregnant beef heifers in response to direct feeding of a mineral and vitamin (VTM) supplement during the first 6 months of gestation. Of note, a well-defined positive impact of maternal VTM supplementation exists on offspring health and performance in beef cattle, and the role of VTM on fetal programming assessed during the first trimester of pregnancy have been documented (Mee et al, 1995; Wilde, 2006; Van Emon et al, 2020; Diniz et al, 2021; Menezes et al, 2021). Questions remain, however, pertaining to whether these maternal VTM supplementation-associated positive outcomes are dependent on VTM-induced alterations of ruminal microbiota.…”
Section: Introductionmentioning
confidence: 99%